Relations of ethnic background, religion, diagnosis, memory, and other variables to presence of shock “therapy” history for a sample of hospitalized mental patients: Preliminary investigation of the lasting effect of shock treatment on behavioral - Morgan, Robert F. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
127 male hospitalized mental patients, aged 20 to 50, were compared on the basis of prior shock treatment experience. None were brain damaged, lobotomized, or had had shock within a year (since lasting effects of shock were the focus of interest). The data suggest 5s were significantly less likely to have had a shock treatment history if they were nonschizophrenic, Catholic, under 30 years, and employed prior to hospital admission; Ss were significantly more likely to have had shock if they were diagnosed schizophrenics (particularly catatonics), without religion, over 35, unemployed prior to hospital admission, and of Japanese ethnic background (Filipino, Hawaiian, Chinese, Korean, U.S. Caucasian ethnic groups showed no significant differences). Marital status, educational level, history of severe depression or suicide attempts were not significantly related to presence or absence of shock. A miniature experiment on Digit Span memory, tested and retested, showed for 4 matched pairs of 5s drawn from the sample, greater mean gains for Ss without shock history'. Seemingly fruitful measures and procedures for further research are discussed.